What Indians eat, and how being unhealthy is easier and cheaper - Swaminathan, Soumya; Singh, Vartika; Subramaniam, Sowmiyaa (Indian Express, 2025)
Food companies must invest in affordable, culturally appropriate, healthy products matching Indian tastes and lifestyles. It requires a whole-of-society engagement.